Two are Better than One: Combining ZnO and MgF2 Nanoparticles Reduces Streptococcus pneumoniae and Staphylococcus aureus Biofilm Formation on Cochlear Implants. (3rd March 2016) - Natan, Michal; Edin, Fredrik; Perkas, Nina; Yacobi, Gila; Perelshtein, Ilana; Segal, Elad; Homsy, Alexandra; Laux, Edith; Keppner, Herbert; Rask‐Andersen, Helge; Gedanken, Aharon; Banin, Ehud
Abstract : Streptococcus pneumoniae ( S. pneumoniae ) and Staphylococcus aureus ( S . aureus ) are considered the most common colonizers of cochlear implants (CI), which have prompted the search for new ways to inhibit their growth and biofilm development. In the current study, CI‐based platforms are prepared and sonochemically coated with ZnO or MgF2 nanoparticles (NPs), two agents previously shown to possess antibacterial properties. Additionally, a method is developed for coating both ZnO and MgF2 on the same platform to achieve synergistic activity against both pathogens. Each surface is characterized, and the optimal conditions for the NP homogenous distribution on the surface are determined. The ZnO‐MgF2 surface significantly reduces the S. pneumoniae and S. aureus biofilm compared with the surfaces coated with either ZnO or MgF2, even though it contains smaller amounts of each NP type. Importantly, leaching assays show that the NPs remain anchored to the surface for at least 7 d. Finally, biocompatibility studies demonstrate that coating with low concentrations of ZnO‐MgF2 results in no toxicity toward primary human fibroblasts from the auditory canal. Taken together, these findings underscore the potential of using NP combinations such as the one presented here to efficiently inhibit bacterial colonization and growth on medical devices such as CIs. Abstract : ZnO‐MgF2 nanoparticles sonochemically coated on cochlear implants (CI) surfaces are superior in reducing biofilm formation by Streptococcus pneumoniae and Staphylococcus aureus compared to just ZnO or MgF2 . A synergistic activity against both bacteria is achieved, if ZnO and MgF2 are applied to the same surface.